2020
DOI: 10.1080/07391102.2020.1817787
|View full text |Cite
|
Sign up to set email alerts
|

Screening of plant-based natural compounds as a potential COVID-19 main protease inhibitor: anin silicodocking and molecular dynamics simulation approach

Abstract: A new strain of coronavirus (CoV) has been identified as SARS-CoV-2, which is responsible for the recent COVID-19 pandemic. Currently, there is no approved vaccine or drug available to combat the pandemic. COVID-19 main protease (M pro) is a key CoV enzyme, which plays an important role in triggering viral replication and transcription, turns it into an attractive target. Therefore, we aim to screen natural products library to find out potential COVID-19 M pro inhibitors. Plant-based natural compounds from Sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(42 citation statements)
references
References 45 publications
0
42
0
Order By: Relevance
“…The activity of plants secondary metabolites against SARS-CoV-2 infection and replication has been extensively reviewed in the last months (da Silva Antonio et al, 2020;Sayed et al, 2020;Weng, 2020) and many studies, based on in silico approaches, suggested some of them as potential drug candidates for COVID-19 treatment (Majumder and Mandal, 2020;Singh et al, 2020). Both viral structural proteins, like Spike, and non-structural proteins, such as 3CLpro, PLpro, and RdRp, have been proposed as valuable targets for anti-SARS-CoV-2 therapeutic strategies.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of plants secondary metabolites against SARS-CoV-2 infection and replication has been extensively reviewed in the last months (da Silva Antonio et al, 2020;Sayed et al, 2020;Weng, 2020) and many studies, based on in silico approaches, suggested some of them as potential drug candidates for COVID-19 treatment (Majumder and Mandal, 2020;Singh et al, 2020). Both viral structural proteins, like Spike, and non-structural proteins, such as 3CLpro, PLpro, and RdRp, have been proposed as valuable targets for anti-SARS-CoV-2 therapeutic strategies.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of plant secondary metabolites against SARS-CoV-2 infection and replication has been extensively reviewed in the last months 55-58 and many studies, based on in silico approaches, suggested some of them as potential drug candidates for COVID-19 treatment 59 . Both viral structural proteins, like Spike, and non-structural proteins, such as 3CL pro , PL pro and RdRp, have been proposed as valuable targets for anti-SARS-CoV-2 therapeutic strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding 3CL pro , recent efforts, have identified potential inhibitors among: alkaloids [ 133 , 134 , 135 , 136 , 137 , 138 ], and especially indole alkaloids [ 139 , 140 , 141 , 142 , 143 , 144 ]; terpenoids [ 138 ], and especially diterpenes [ 133 , 145 ]; sesquiterpenes [ 134 , 146 , 147 ], sesquiterpene lactones [ 148 ], and triterpenes [ 133 , 136 , 140 , 149 ]; anthocyanins [ 150 , 151 ] and proanthocyanidins [ 152 , 153 ]; ellagitannins [ 153 , 154 ]; flavonoids [ 133 , 137 , 140 , 144 , 147 , 148 , 152 , 155 , 156 , 157 , 158 , 159 , 160 , 161 ], biflavonoids [ 162 ], and macrocyclic flavonoids [ 148 ]; isoflavones [ 144 , 148 ]; chalcones […”
Section: Nps With Anti-hcov Potentialmentioning
confidence: 99%